Plasma Concentration of Cortisol and Progesterone During Periparturient Period in West African Dwarf Goats Reared in Nigeria - Nwosu, E.U; Babatunde, I.A.; Olaromade, Z.O.; Essien, K.F. (Nigerian Journal of Animal Science, 2026)
In goat, progesterone (P4) aids implantation process and maintenance of pregnancy. Cortisol may assist in parturition because it aids in activating Prostaglandin F2α (PGF2a). This study aimed at determining the periparturient plasma P4 and cortisol concentration in pregnant West African Dwarf (WAD) does. A total of fourteen (14) cycling and healthy WAD does were used. Blood samples were collected from them in the morning prior to feeding and emptied into a sterile tubes containing Ethylene Diamine-Tetra-Acetic Acid (EDTA). The sampling was done four weeks prior to the expected day of kidding and four weeks after kidding. The collected blood samples were centrifuged to recover plasma and frozen at -20_ for hormonal assay. Enzyme-linked immunosorbent assay was used for the P4 and cortisol concentrations determination. The data analyses were carried out using SPSS v.20.0. The comparison among the different physiological periods showed that P4 concentrations during prepartum phase is higher (P<0.05) compared to its concentrations during puerperium phase. During prepartum period, the levels of P4 declined consistently from 2.49 ng/ml in week four to 2.15 ng/ml in the last week before parturition. P4 decline from (1.66 ng/ml) in the first week of post parturition, thereafter, remained steady (1.65 ng/ml) until third week and declined to 1.42 ng/ml in the fourth week post-partum. The results showed non-significant (P>0.05) differences in plasma cortisol among the different physiological periods. It was concluded that, progesterone is necessary for maintenance of pregnancy and the decline aids parturition in WAD does.